2023
DOI: 10.1002/eco.2588
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of hydrology, sewage and industries in distribution and migration pathways of heavy metals at spatial scale of China's brownfields

Jie‐Yu Yu,
Jian‐Jian Wang,
Wei Zhang
et al.

Abstract: Hydrologic dynamics, sewage and industries determine the distribution and migration pathways of heavy metals in the natural environments including soils across the urbanized area. In this study, 323 stratified soil samples from a brownfield in Jiangsu Province, China, were collected to assess the heavy metals (Cu, Ni, Pb, Cd, As and Hg) contaminations. Contamination factor (Cfi), Nemerow pollution index (PIN) and enrichment factor (EFi) were evaluated to assess the heavy metal pollution, while sources of pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The study of Liu et al [59] on the Zengtang Reservoir in the Guangzhou City also confirms that anthropogenic interventions in production activities can greatly increase the amount of nutrients and heavy metals entering a water body, leading to reservoir eutrophication and ecosystem degradation. Other studies [60,61] suggest that heavy metals enter lakes through various pathways. For example, Cu and Zn from industrial and waste pollution [62] and agricultural fertilizer residues, as well as Pb from automobile exhaust emissions [57], are considered solid and persistent pollutants in many aquatic ecosystems [63].…”
Section: Historical Environmental Change and Its Driving Factors In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Liu et al [59] on the Zengtang Reservoir in the Guangzhou City also confirms that anthropogenic interventions in production activities can greatly increase the amount of nutrients and heavy metals entering a water body, leading to reservoir eutrophication and ecosystem degradation. Other studies [60,61] suggest that heavy metals enter lakes through various pathways. For example, Cu and Zn from industrial and waste pollution [62] and agricultural fertilizer residues, as well as Pb from automobile exhaust emissions [57], are considered solid and persistent pollutants in many aquatic ecosystems [63].…”
Section: Historical Environmental Change and Its Driving Factors In T...mentioning
confidence: 99%
“…For example, Cu and Zn from industrial and waste pollution [62] and agricultural fertilizer residues, as well as Pb from automobile exhaust emissions [57], are considered solid and persistent pollutants in many aquatic ecosystems [63]. A study of stratified soil samples from a brownfield in Jiangsu Province showed that the pathway of heavy metal (Cu, Ni, Pb, Cd, As and Hg) contamination is largely dependent on agricultural discharge from upstream river catchments [61].…”
Section: Historical Environmental Change and Its Driving Factors In T...mentioning
confidence: 99%
“…For instance, the habitat extent of larval and juvenile silvery minnow population in Rio Grande River (USA), in the special issue, has been successfully estimated using hydrology statistics, inundation extents based on hydraulic modelling and areal habitat availability based on a habitat suitability index curve, demonstrating a robustness in fish habitat management by validating the ecological model (Harris et al, 2024). (Yu et al, 2023).…”
mentioning
confidence: 99%